SPACE-CENTRIC CONCEPT TO ANSWER TOMORROW SPACE CHALLENGE: A SMALL STEP FOR FUTURE SPACE LAW - Taufik Rachmat Nugraha (Diponegoro Law Review, 2021)
Space activities have shown significant progress since they begin in the late '50s. Under current development, the U.S. with Artemis program and Luxembourg with its space mining program will enhance their outer space involvement. Most of those programs will elevate private sector involvement. Furthermore, the future space program will mainly intersect with the space environment as the primary consideration. It remains high-risk activities that could have catastrophic results if not regulated immediately. However, the current existing space law began obsolete because it was composed more than 50 years ago and too geocentric by putting the earth as the primary protection area. Consequently, existing space law could not govern future space programs properly, including protecting the space environment defense, Etc. Afterward, this paper will introduce the space-centric concept. Space-centric concepts create to answer future space challenges from legal perspectives. This concept emphasizes how future regulation and policy should cover all space objects equally, recalling outer space is vulnerable to such activities by humans, and how the best way to mitigate unforeseeable calamity on outer space.